Effects of entrepreneurship education and green entrepreneurial self-efficacy on green entrepreneurial intentions - Leny Agustina Endarwati (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2025)
Abstrak: Penelitian ini bertujuan untuk mengetahui Pengaruh Entrepreneurship Education dan Green Entrepreneurial Self-Efficacy terhadap Green Entrepreneurial Intentions pada mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif korelasional, dengan teknik pengambilan sampel yaitu stratified sampling dan incidental sampling. Sampel yang digunakan dalam penelitian ini adalah sebanyak 120 mahasiswa. Teknik pengumpulan data menggunakan kuesioner. Teknik analisis data yang digunakan adalah analisis dengan pendekatan PLS-SEM. Temuan penelitian ini menunjukkan bahwa entrepreneurship education berpengaruh positif signifikan terhadap green entrepreneurial intentions dan green entrepreneurial self-efficacy. Green entrepreneurial self-efficacy juga ditemukan memiiki pengaruh positif dan signifikan terhadap green entrepreneurial intentions mahasiswa. Selain itu, dengan pengaruh mediasi oleh green entrepreneurial self-efficacy diantara entrepreneurship education dan green entrepreneurial intentions menunjukkan hasil yang positif dan signifikan.  Kata kunci: efikasi diri kewirausahaan hijau; niat kewirausahaan hijau; pendidikan kewirausahaan Abstract: This study aims to investigate the influence of entrepreneurship education and green entrepreneurial self-efficacy on green entrepreneurial intentions among university students. This research employed a quantitative correlational approach, utilizing stratified sampling and incidental sampling techniques. The sample consisted of 120 students, with data collected through questionnaires and analyzed using PLS-SEM approach. Findings indicate that entrepreneurship education has a significant positive effect on both green entrepreneurial intentions and green entrepreneurial self-efficacy. Green entrepreneurial self-efficacy was also found to have a positive and significant effect on students' green entrepreneurial intentions. Additionally, the mediation effect of green entrepreneurial self-efficacy between entrepreneurship education and green entrepreneurial intentions showed positive and significant results. These findings contribute to understanding the mechanisms through which entrepreneurship education influences sustainable business intentions and highlight the critical role of self-efficacy in fostering environmentally conscious entrepreneurial behavior among university students. Keywords: entrepreneurship education; green entrepreneurial intentions;  green entrepreneurial self-efficacy